Method for the detection of fatigue during gymnastics training - Beatty, K. T.; McIntosh, A. S.; Frechede, B. O. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to determine if acceleration measured at the pelvis was a suitable indicator of fatigue in gymnasts. Fourteen gymnasts performed vertical jumps and drop landings pre and post a fatiguing jumping activity. Peak acceleration during landing for jumps and drops increased significantly after fatiguing activity. Acceleration is a tool that can be collected with limited disruption to gymnastics training and an increase in peak acceleration during landing of simple jumps appears to be a useful tool for determining whether gymnasts are fatigued.